2020
DOI: 10.1038/s41598-020-60225-w
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the intimin gene (eae) in non-O157 Shiga toxin-producing Escherichia coli strains in China

Abstract: Shiga toxin-producing Escherichia coli (STEC) is an important foodborne pathogen. The increasing incidence of non-O157 STEC has posed a great risk to public health. Besides the Shiga toxin (Stx), the adherence factor, intimin, coded by eae gene plays a critical role in STEC pathogenesis. In this study, we investigated the prevalence and polymorphisms of eae gene in non-O157 STEC strains isolated from different sources in China. Among 735 non-O157 STEC strains, eae was present in 70 (9.5%) strains. Eighteen dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 49 publications
4
22
1
Order By: Relevance
“…The major stx subtypes of the eae positive isolates were stx 1a and stx 2c , which were prevalent in the HUS related isolates (Brooks et al, 2005;Byrne et al, 2020). These data were significantly different from recent large scale surveillance studies in China, which showed that most STEC isolates were eae negative (Bai et al, 2015;Yang et al, 2020b;Su et al, 2021). Our data demonstrated that the eae positive highly pathogenic STEC isolates existed in the retail beef samples from China, and their recovery was relied on the use of proper and effective isolation methods.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The major stx subtypes of the eae positive isolates were stx 1a and stx 2c , which were prevalent in the HUS related isolates (Brooks et al, 2005;Byrne et al, 2020). These data were significantly different from recent large scale surveillance studies in China, which showed that most STEC isolates were eae negative (Bai et al, 2015;Yang et al, 2020b;Su et al, 2021). Our data demonstrated that the eae positive highly pathogenic STEC isolates existed in the retail beef samples from China, and their recovery was relied on the use of proper and effective isolation methods.…”
Section: Discussioncontrasting
confidence: 89%
“…In this study, all isolates of the top 3 serotypes (n = 34) were eae positive, but only 2 eae positive isolates were identified among 48 isolates in the other serotypes. Similar eae positive STEC serotype distribution pattern has been reported in recent studies, and these serotypes were also found among patients from China (Bai et al, 2016;Yang et al, 2020b). The major stx subtypes of the eae positive isolates were stx 1a and stx 2c , which were prevalent in the HUS related isolates (Brooks et al, 2005;Byrne et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, we detected one isolate with eae, an intimin-encoding gene. The protein, encoded by eae , plays a critical role on the intestinal colonisation and, therefore, STEC (shiga toxin-producing E. coli ) or another aggregative E. coli pathogenesis [ 61 ]. Some isolates harboured toxin genes or toxin subunits such as astA ( n = 16), cdtA ( n = 3), cnf1 ( n = 3), eltA ( n = 1), and faeC ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Ninety-two percent (23/25) of the atypical EPEC of group A carried eae-ρ, first described in 2006 in a O21:[h5] EPEC strain [19]. The eae subtypes γ1, β1, ε, and θ are known to be associated with major EHEC serogroups [20], whereas the eae-ρ subtype is uncommon [21] and exceptionally associated with stx genes, especially in humans, with only one strain reported to date (O180:H2, stx2a, ST301) [22]. We thus report the second EHEC harboring eae-ρ (93271), associated here with the stx1a subtype.…”
Section: Discussionmentioning
confidence: 99%